2009
DOI: 10.1124/mol.109.058289
|View full text |Cite
|
Sign up to set email alerts
|

An Epilepsy-Related Region in the GABAA Receptor Mediates Long-Distance Effects on GABA and Benzodiazepine Binding Sites

Abstract: The GABA A receptor mutation ␥ 2 R43Q causes absence epilepsy in humans. Homology modeling suggests that ␥ 2 Arg43, ␥ 2 Glu178, and ␤ 2 Arg117 participate in a salt-bridge network linking the ␥ 2 and ␤ 2 subunits. Here we show that several mutations at these locations exert similar long-distance effects on other intersubunit interfaces involved in GABA and benzodiazepine binding. These mutations alter GABA-evoked receptor kinetics by slowing deactivation, enhancing desensitization, or both. Kinetic modeling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 40 publications
3
54
0
Order By: Relevance
“…We used a simplified model of GABA A receptor behavior ( Fig. 6) that had been described previously (Jones et al, 1998;Wagner et al, 2004;Goldschen-Ohm et al, 2010). Although we considered more complex variations of this model that included additional desensitized and open states, the simplified model was equally suitable to recapitulate our data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a simplified model of GABA A receptor behavior ( Fig. 6) that had been described previously (Jones et al, 1998;Wagner et al, 2004;Goldschen-Ohm et al, 2010). Although we considered more complex variations of this model that included additional desensitized and open states, the simplified model was equally suitable to recapitulate our data.…”
Section: Methodsmentioning
confidence: 99%
“…Although we considered more complex variations of this model that included additional desensitized and open states, the simplified model was equally suitable to recapitulate our data. During optimization the rate constant k on and P o-max were constrained to the value obtained from experiments in this study; all other parameters were initially set to values reported by Goldschen-Ohm et al (2010) and were unconstrained. Current responses from 3-and 500-ms pulses of saturating GABA were simultaneously fit for each patch.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it is believed that BZDs exert their allosteric effects by either shifting the GABA A R closed to open-state channel equilibrium (Downing et al, 2005;Rü sch and Forman, 2005;Campo-Soria et al, 2006) or altering the receptor's microscopic binding affinity for GABA (Twyman et al, 1989;Rogers et al, 1994;Lavoie and Twyman, 1996;Mellor and Randall, 1997;Thompson et al, 1999;Goldschen-Ohm et al, 2010). Regardless of the mechanism, BZD binding to the receptor is the initial perturbation that triggers structural rearrangements in the protein that result in modulation of GABA A R function.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the binding rate, we could not examine this directly, but instead we asked whether such a hypothesis could explain our observations using a kinetic model shown previously to account for multiple aspects of GABA A receptor behavior (Fig. 7A) (Jones et al, 1998;Wagner et al, 2004;Goldschen-Ohm et al, 2010).…”
Section: Role Of Arginines In Agonist and Antagonist Binding 653mentioning
confidence: 99%